The natural history of HIV-1 subtype e infection in young men in Thailand with up to 14 years of follow-up - Ram Rangsin (2018)
OBJECTIVE: We evaluated the progression to AIDS and death among 228 men who seroconverted within a 6-month window when in the Royal Thai Army between 1991 and 1995. DESIGN AND METHODS: Men (N = 228) who seroconverted to HIV at 21-23 years of age between 1991 and 1995 were evaluated up to 14 years after HIV seroconversion. The seroconverters were matched with men who were seronegative when they were discharged from the military. In 2005-2006, the vital status was determined through the national mortality database and survivors were contacted for follow-up clinical and immunological assessment. Death certificates, medical records and next of kin interviews were used to evaluate the causes of death. RESULTS: As of March 2006, among 228 seroconverters, 56 (24.6%) were alive, 171 (75.0%) had died and one (0.4%) had undetermined status. Among 255 HIV-seronegative individuals at baseline, 15 (5.9%) had died. The median time from HIV seroconversion to death was 7.8 years. The median time to AIDS death was 8.4 years. The median times from seroconversion to clinical AIDS and a CD4 cell count less than 200 cells/μl were 7.2 years and 6.5 years, respectively. The median time from seroconversion to World Health Organization criteria for antiretroviral therapy was 6.3 years. CONCLUSION: Our data indicate a more rapid progression to AIDS and death after HIV-1 infection among young Thai men than has been reported in similar aged men who were HAART-naive in western high income countries. © 2007 Lippincott Williams & Wilkins, Inc.